New Insights of Response Surface Methodology Approach in Optimizing Total Phenolic Content of Zanthoxylum acanthopodium DC. Fruit Extracted Using Microwave-Assisted Extraction and the Impact to Antioxidant Activity - Sumaiyah, Sumaiyah; Murwanti, Retno; Illian, Didi Nurhadi; Lubis, Muhammad Fauzan; Tampubolon, Keshia (Universitas Gadjah Mada, 2024)
Zanthoxylum acanthopodium DC., a unique spice plant from North Sumatra, is rich in beneficial secondary metabolites, particularly phenolic compounds. This study utilized the microwave-assisted extraction method to enhance the extraction of these bioactive compounds. The goal was to determine the optimal extraction conditions, including solvent concentration (X1), microwave power (X2), and extraction time (X3) to maximize the total phenolic content (TPC) of Z. acanthopodium fruit. A Box-Behnken design, part of response surface methodology, was used with three factors at three levels: X1 (50%, 75%, and 100% ethanol in water), X2 (180, 300, and 450 W), and X3 (3, 8.5, and 14 min). The phenolic compounds in the optimized extract were identified using LC-HRMS, and its antioxidant activity was measured using radical scavenging activity assays. The statistical analysis indicated a significant quadratic model (p-value < 0.05), with a high R2 of 86.25%. Optimal conditions for maximum TPC (159.637 ± 5.72 mg GAE/g) were achieved with 50% ethanol, 450 W, and 8.5 min, outperforming conventional extraction methods. Compared to the non-optimized extract, the optimized extract also exhibited strong antioxidant activity, particularly in DPPH radical inhibition. This method successfully optimized TPC in Z. acanthopodium fruit, enhancing its antioxidant properties.